Experimental Study of Screw Withdrawal in Acacia Cross-Laminated Timber (CLT) - Ferry, Ferry; Awaludin, Ali; Irawati, Inggar Septhia (Universitas Ibn Khaldun Bogor, 2025)
This study examines the screw withdrawal strength in Acacia Cross-Laminated Timber (CLT) using screws of 5 mm diameter. CLT, typically made from softwoods, is gaining interest with hardwoods like Acacia for enhanced structural performance. The study evaluated screw withdrawal resistance across face, edge, and end grain orientations, following EN 1382 standards. The results showed that the face grain orientation exhibited the highest average withdrawal strength of 6.7 kN with a specific strength of 10.6 N/mm², while the edge grain had 6.5 kN and 10.3 N/mm². The end grain had the lowest strength with an average of 4.0 kN and 6.3 N/mm². Additionally, higher wood density was found to increase withdrawal strength, with heavier samples showing greater performance. These findings emphasize Acacia’s potential for structurally optimized CLT applications.